Anti‐adipogenic and antiviral effects of l‐carnitine on hepatitis C virus infection. Issue 5 (3rd October 2016) - Tsukuda, Yoko; Suda, Goki; Tsunematsu, Seiji; Ito, Jun; Sato, Fumiyuki; Terashita, Katsumi; Nakai, Masato; Sho, Takuya; Maehara, Osamu; Shimazaki, Tomoe; Kimura, Megumi; Morikawa, Kenichi; et al.
Abstract : Hepatitis C virus (HCV) has been reported to hijack fatty acid metabolism in infected hepatocytes, taking advantage of lipid droplets for virus assembly. In this study, we analyzed the anti‐HCV activity ofl ‐carnitine, a substance involved in the transport of fatty acids into mitochondria. JFH‐1 or HCV replicon‐transfected Huh7.5.1 cells were treated with or withoutl ‐carnitine to examine its anti‐HCV effects. The effects ofl ‐carnitine on HCV entry, HCV‐induced adipogenesis and lipid droplet formation, and HCV‐induced oxidative stress were examined. Treatment of JFH‐1‐infected cells withl ‐carnitine inhibited HCV propagation in a concentration‐dependent manner. In contrast, l ‐carnitine had no anti‐HCV activity in the HCV replicon system, which is lacking viral assembly. In addition, l ‐carnitine did not affect HCV entry. However, l ‐carnitine treatment decreased intracellular lipid droplets, which are crucial for HCV assembly in JFH‐1‐infected cells. The expression level of CPT‐1 was decreased in JFH‐1‐infected cells, andl ‐carnitine treatment restored this expression. HCV‐infected cells exhibited increased production of reactive oxygen species and glutathione oxidation.l ‐carnitine decreased oxidative stress induced by JFH‐1‐infection, as shown by glutathione/glutathione disulfide assays and MitoSOX staining.l ‐carnitine exhibited anti‐HCV activity, possibly by inhibiting HCV assembly and through its anti‐adipogenic activity in HCV‐infected cells. Moreover, l ‐carnitine has antioxidant properties in HCV‐infected hepatocytes. Overall, these results indicated thatl ‐carnitine may be an effective adjunctive agent in antiviral therapies to treat chronic hepatitis C. J. Med. Virol. 89:857–866, 2017 . © 2016 Wiley Periodicals, Inc.